The Influence of Food Security Program Through Arts and Culture Towards Sustainable Development in Mahulu District, East Kalimantan Province - Rahcmad Budi Suharto; Geh, Bonifasius Belawan; Hasid, Zamruddin; Amalia, Siti (International Journal of Economics (IJEC), 2023)
This research examines the implementation of the "Urip Kerimaan" Food Security Program in Mahulu Regency, East Kalimantan Province, since 2021. This program aims to increase food independence by focusing on developing modern and organic dry land agriculture. The program steps involve opening 500 hectares of new land in 50 villages, with capital support, community-based agricultural technology management, and outreach for farmers. This research uses a conceptual framework that includes aspects of the Food Security Program (X), Arts and Culture (Urip Kerimaan) (M), and Sustainable Development (Y). This research method involves collecting quantitative and qualitative data from 1009 farmers involved in the Food Security Program. The research results show that the Food Security Program has a positive and significant impact on Sustainable Development, as well as on Arts and Culture. The Food Security Program has made a positive contribution to increasing the area of rice fields, rice production and the number of farmers in villages. Apart from that, Arts and Culture are also closely related to this program, with increasing public interest in various cultural expressions such as music, crafts and dance, which then influences Sustainable Development.